Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

let f(x)=x+8 and g(x)=x^2 -6x-7. find f(g(2))

Sagot :

[tex]f(g(2))=2^2-6\cdot2-7+8=4-12+1=-7[/tex]
[tex]f(x)=x+8\\\\g(x)=x^2-6x-7\\\\f(g(x))=(x^2-6x-7)+8=x^2-6x+1\\\\f(g(2))=2^2-6\cdot2+1=4-12+1=-7\\\\Solution:f(g(2))=-7[/tex]